Identification and distribution of acetylcholinesterase inhibitory alkaloids from different locations in peninsular Malaysia / Nurul Ain Mohd Nor - Mohd Nor, Nurul Ain (2018)
A series of Lycopodium alkaloids, namely 6β-hydroxyhuperzine A (96), 16-hydroxyl huperzine A (318) and huperzine A (93), have been isolated from Huperzia phlegmaria. Their structure and relative stereo chemistry were elucidated on the basis of their spectral data and chemical correlations. A simple and reliable high performance liquid chromatography (HPLC) method has been established for the analysis of the isolated compounds. The recovery rates were between 91 – 111 %. The within- and between-day precisions, expressed as R.S.D ranged from 0.5 % to 2.6 %. Good linear regression was observed, r2=0.999. The results demonstrate that this method is simple and suitable for quality control of this traditional Chinese medicinal herb. Additionally, the acetylcholinesterase inhibitory activity of isolated compounds was evaluated. The inhibition of cholinesterase activity was determined based on Ellman’s colorometric method. Colorimetric measurements were measured with a microplate reader at a wavelength of 405 nm. Galanthamine was used as a positive control. In conclusion, 6β-hydroxyhuperzine A (96) exhibited weak acetylcholinesterase inhibitory activity, while 16-hydroxyl huperzine A (318) did not show inhibitory effect (>200 μM) compared to huperzine A (93).